2021
DOI: 10.3116/16091833/22/3/123/2021
|View full text |Cite
|
Sign up to set email alerts
|

Cubic�quartic optical solitons in Lakshmanan�Porsezian�Daniel model derived with semi-inverse variational principle

Abstract: We retrieve analytically a bright 1-soliton solution to a perturbed cubic−quartic Lakshmanan-Porsezian-Daniel model, using a semi-inverse variational principle. The perturbation terms are considered arising from the condition of maximum allowable intensity. The restrictions imposed by integrability considerations on the model parameters are enlisted. It is important that the other analytical approaches available fail to recover the analytical bright-soliton solution to the model with the maximum allowable inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…It is also relevant to mention that the functional form of the interacting periodic wave and breathers wave solutions (15) and ( 20) are also different from those obtained very recently by Ma and Li [47] and previously by Kevrekidis et al [32] as well as Alejo and Muñoz. [48] This illustrates the richness of nonlinear systems modeled by the mKdV equation, which is often measured by the variety of wave structures that the medium can support.…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…It is also relevant to mention that the functional form of the interacting periodic wave and breathers wave solutions (15) and ( 20) are also different from those obtained very recently by Ma and Li [47] and previously by Kevrekidis et al [32] as well as Alejo and Muñoz. [48] This illustrates the richness of nonlinear systems modeled by the mKdV equation, which is often measured by the variety of wave structures that the medium can support.…”
mentioning
confidence: 59%
“…Additionally, we have found that the existence of these new structures depend drastically on the type of nonlinearity of the nonlinear medium (a self-focusing or defocusing one). These results constitute the analytical demonstration of existence of new closed form solutions in the form of a pair interacting solitons (10), interacting periodic waves (15) and breathers waves (20) to the mKdV equation. The wide applicability of the mKdV equation to describe evolution dynamics of nonlinear waves in a variety of different physical media allows the usefulness of our results to recognize various nonlinear phenomena and dynamical processes in these systems.…”
mentioning
confidence: 59%
See 3 more Smart Citations